Implementation of Stunting Policy to Improve Public Awareness and Accelerate Integrated Stunting Reduction in Jombang Regency - Muhammad Mujtaba Mitra Zuana; Muhammad Baiqun Isbahi; Mohamad Toha (Sahwahita: Community Engagement Journal, 2025)
This program responds to the issue of stunting in Jombang Regency, namely the condition of growth failure in children due to malnutrition in the first 1,000 days of life, which threatens the quality of the generation facing 2045. Although the prevalence of stunting in Jombang (5.85% in early 2024) was below the national target (<14%), efforts to accelerate reduction are still needed in accordance with Regent Regulation No. 4 of 2022. This qualitative research aims to identify and analyze the implementation of integrated stunting reduction policies and their inhibiting factors. Data were collected through observation, interviews, and document studies, then analyzed using Soren C. Winter's policy implementation theory which emphasizes three behavioral aspects: inter-organizational relationships, lower-level bureaucrats, and target groups. The results show that implementation is running quite well, as evidenced by the decrease in cases from 5,509 (2022) to 3,428 (September 2024). However, several indicators have not reached the target, especially related to the suboptimal behavior of lower-level bureaucrats. The identified obstacles serve as learning materials for improvement. Therefore, it is recommended that the performance of policy makers be optimized and the human resource capacity of lower-level implementers be enhanced. Collaboration with the public and private sectors also needs to be strengthened to optimize comprehensive preventive measures for stunting.